Балти на території України за доби Київської Русі. Антропологічний аспект - Рудич, Т.О. (Археологія і давня історія України, 2020)
У статті на матеріалах антропології розглянуто питання фізичної присутності вихідців з балтських груп на землях України за доби Київської Русі. The morphological similarities between the people buried in the cemeteries of Old Rus period from the territory of Ukraine and Balts population of the 12th—13th centuries were found. The samples used in this research are combined series of sculls from Volyn and drevlian’s fields, the group from Vozviagel, the little series from Jagniatyn, the group from Zelenyi Gai (barrows), and the group from Medzybizh.